Identification of new phase II metabolites of xanthohumol in rat in vivo biotransformation of hop extracts using high-performance liquid chromatography electrospray ionization tandem mass spectrometry - Jirásko, Robert; Holcapek, Michal; Vrublová, Eva; Ulrichová, Jitka; Simánek, Vilím (Journal of chromatography. A, 2010)
Polyphenolic compounds occurring in hop extracts and their phases I and II metabolites formed during in vivo rat biotransformation have been analyzed using HPLC/MS/MS with electrospray ionization (ESI). Two main groups of polyphenolics are present in the hops, i.e., xanthohumol related compounds and so called alpha- and beta-bitter acids (humulones and lupulones). In our study, hybrid quadrupole-time-of-flight (QqTOF) analyzer is used for the identification of both natural phenolics and their metabolites due to the possibility of accurate mass measurements in full scan and tandem mass spectra supported by MS(n) data obtained with the ion trap analyzer. Both ESI polarity modes are used for the determination of molecular weights based on [M+H](+) and [M-H](-) ions in the full scan spectra and the structural information in subsequent tandem mass spectra. The emphasis is given on the elemental composition determination of individual metabolites based on accurate masses typically better than 5ppm even with the external calibration. Advanced software tools are used for the metabolite identification using the comparison of the blank chromatogram with the real incubation sample together with the software prediction and detection of possible metabolites. Chromatograms of rat incubations are also compared with chromatograms of pure rat feed, rat feed enriched with hop extracts and the placebo experiment. More than ten compounds originating from the hops are identified in rat feces, two of them belong to phase I metabolites and five compounds are phase II metabolites.
Keywords: flavonoidy; Chromatography, High Pressure Liquid; Flavonoids; Plant Extracts; Biotransformation; feces; Animal Feed; molekulová hmotnost; Humulus; krysa rodu Rattus; zvířata; propiofenony; rostlinné extrakty; molekulární struktura; Propiophenones; potkani Wistar; Molecular Structure; Feces; hmotnostní spektrometrie s elektrosprejovou ionizací; Rats, Wistar; Male; krmivo pro zvířata; biotransformace; Rats; Spectrometry, Mass, Electrospray Ionization; Animals; mužské pohlaví; vysokoúčinná kapalinová chromatografie; Molecular Weight